Identification of Students' Misconceptions on Hydrocarbon Material Using a Four-Tier Multiple Choice Diagnostic Test - Reni Arif Karini; Retno Aliyatul Fikroh; Vika Puji Cahyani (Universitas Pendidikan Ganesha, 2022)
As one of the sciences, some students consider chemistry complex and abstract, so many misconceptions arise. One of the chemistry topics that cause many misconceptions is hydrocarbons. A misconception is an understanding of concepts in students' minds that are contrary to scientific concepts. This research aimed to identify the student’s understanding and misconception of hydrocarbon. The study was qualitative descriptive research. Qualitative descriptive research was used to identify student misconceptions using the four-tier test. The sample of the research was 24 students. The instruments used in this research are four test levels which include (1) multiple-choice, (2) confidence rating of the answer beliefs, (3) reason for the answer, and (4) confidence rating of the reasoning. The result shows that 24,7% of students well-understood hydrocarbon concepts, 32,1% do not understand, and 43,2% have misconceptions. Misconceptions in this research are divided into three categories: low, moderate, and high. The students experience misconceptions with high criteria on the concept reaction of hydrocarbon (66,7%), moderate criteria on the concept of determining hydrocarbon compound (31,3%), the nomenclature of hydrocarbon compound (56,3%), types atom carbon (37,5%), Physical and Chemical Properties (45,8%), isomers (47,9%) and low criteria on the concept of characteristics of carbon atoms (16,7%).